Reliability (Revalidation) of MSU MRI Classification of Lumbar Disc Herniation in 100 Patients Series: Severity and Objective Surgical Criteria - Emad Abouelmaaty (Egyptian Spine Association, 2016)
Background Data: Success rate of discectomy is greatly variable between surgeons due to lack of clear categorization of lumbar disc patients. Valid radiological objective criteria are required especially for patients with uncertain surgical indication to help in pre-operative patient assessment, surgical selection and research of post-operative outcomes of comparable level of pathology. MSU Classification reports size and location in three precise increments, described simply 1-2-3 and A-B-C providing clear objective classification of disc herniation resulting in excellent interexaminar reliability. Purpose To test reliability of MSU MRI classification of lumbar disc herniation in helping surgical selection and correlation with preoperative clinical presentation and postoperative clinical and functional outcome. Study Design Observational analytic retrospective study. Patients and Methods Retrospective investigations of one hundred patients who underwent lumbar discectomy at Ain Shams University between January 2014 and June 2015 in term of MSU classification. Results Only 2 patients (2%) in our series had grade 1-A. All other 98 patients had MSU grades with size 2 or 3 and/or B or C location or 2 or 3 combination of horizontal disc locations (A, B or C). Two cases of unintended durotomy occurred in MSU grade 3-AB (40%) and the other 3 cases occurred in grade 2-AB (60%). One case of CSF leak occurred in 3-AB herniated disc lesion (50%) and another one in 2-AB lesion (50%). Twelve patients (12%) developed recurrent sciatica with mean interval of 47.92 weeks after first disc surgery. Only 5 patients (5%) underwent second disc surgery with mean interval of 6.2 months. 95 patients (95%) had good to excellent result. Conclusion: MSU classification provides solid, universal and objective radiological description of lumbar disc herniation helping patient selection for surgery. (2016ESJ097)